The polarity effect of nanosecond voltage pulses on the propagation of streamers in a point-to-plane gap filled with air. (5th March 2020) - Beloplotov, Dmitry V.; Genin, Dmitry E.; Pechenitsin, Dmitry S.
Abstract: The results of experimental studies of the effect of polarity on the streamer velocity at various voltage amplitudes are presented. In the experiments, nanosecond voltage pulses were applied across an 8.5 mm point-to-plane gap filled with air at a pressure of 100 kPa. The formation of positive and negative streamers has been experimentally studied using a HSFC-PRO four-channel ICCD camera and a Hamamatsu C10910-05 streak camera. Waveforms of voltage and discharge current pulses were also recorded. The propagation velocity of streamers was estimated by streak images. It was found that a negative streamer crosses the gap faster than a positive one. This is most likely due to the presence of runaway electrons with the negative polarity of a pointed electrode. The experiment showed that runaway electrons are generated before the formation of a negative streamer. Runaway electrons can preionize the gas in the gap.